ANALISIS KEMAMPUAN GURU SEKOLAH DASAR TENTANG PENGGUNAAN APLIKASI MACROMEDIA FLASH GUGUS 2 KECAMATAN TAMPAN KOTA PEKANBARU - Ulfa, Nabila; Kurniaman, Otang; Adi Putra, Jaya (Jurnal Ilmiah Aquinas, 2021)
The development of science and technology is increasingly encouraging renewal efforts in the use of technological results in the learning process. Teachers are required to be able to understand and use the available tools in an effort to achieve the expected teaching goals. This study aims to determine the teacher's knowledge about the use of macromedia flash applications. Based on the results in several schools in general, teachers are not well acquainted with the application of macromedia flash, until it was found that there were still many teachers who taught using conventional methods. With such conditions, it certainly has an impact on low student learning outcomes.